2017
DOI: 10.1093/cid/cix301
|View full text |Cite
|
Sign up to set email alerts
|

Gray and White Matter Abnormalities in Treated Human Immunodeficiency Virus Disease and Their Relationship to Cognitive Function

Abstract: Cognitive impairment, lower gray matter volume, and white matter microstructural abnormalities were evident in HIV-infected individuals despite fully suppressive antiretroviral therapy. White matter abnormalities appear to be a particularly important determinant of cognitive dysfunction seen in well-treated HIV-infected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 40 publications
17
66
0
Order By: Relevance
“…This may reflect the more appropriate selection of an HIVnegative control group with similar lifestyles to the PLWH. Of note, our findings are consistent with those from the comorbidity in relation to HIV/AIDS study [32,33] in which baseline differences between PLWH and comparable controls did not increase with longer follow-up. The link between HIV infection and depression is likely to be bi-directional and multifactorial, involving both biological and psychosocial/social factors [7].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This may reflect the more appropriate selection of an HIVnegative control group with similar lifestyles to the PLWH. Of note, our findings are consistent with those from the comorbidity in relation to HIV/AIDS study [32,33] in which baseline differences between PLWH and comparable controls did not increase with longer follow-up. The link between HIV infection and depression is likely to be bi-directional and multifactorial, involving both biological and psychosocial/social factors [7].…”
Section: Discussionsupporting
confidence: 90%
“…This may reflect the more appropriate selection of an HIV‐negative control group with similar lifestyles to the PLWH. Of note, our findings are consistent with those from the co‐morbidity in relation to HIV/AIDS study in which baseline differences between PLWH and comparable controls did not increase with longer follow‐up.…”
Section: Discussionsupporting
confidence: 89%
“…Another main strength is the participation of SHM and the ATHENA cohort in regional, national and international scientific research collaborations. There is close collaboration with the Academic Medical Center of the University of Amsterdam, the Public Health Service Amsterdam through the Amsterdam Cohort Studies (ACS) 36 ; the MSM Observational Study of Acute Infection with Hepatitis C (MOSAIC) 32 ; Co-morbidity and Ageing with HIV (AGE h IV) cohort study 37 ; EU-funded Co-morbidity in Relation to AIDS (COBRA) programme 38 ; and the HIV Transmission Elimination Amsterdam (H-TEAM) initiative. 39 ATHENA collaborates with other research groups and observational cohorts in western Europe, the USA and Canada.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…[41, 85-88] One study found widespread white matter abnormalities that correlated with cognitive impairment. [88] In contrast, cardiovascular risk factors and duration of past immune deficiency but not cognitive impairment were found to be associated with white matter injury among men with well controlled HIV infection.…”
Section: Neuroimagingmentioning
confidence: 99%
“…[41, 85-88] One study found widespread white matter abnormalities that correlated with cognitive impairment. [88] In contrast, cardiovascular risk factors and duration of past immune deficiency but not cognitive impairment were found to be associated with white matter injury among men with well controlled HIV infection. [87] Another study investigated white matter abnormalities in 56 HIV-infected elders compared to 31 matched controls reporting widespread fractional anisotropy (FA) decreases and increased mean diffusivity (MD) in areas including the corpus callosum, splenium, body of the genu, tapetum of the corpus callosum, as well as the anterior, superior and posterior corona radiata.…”
Section: Neuroimagingmentioning
confidence: 99%